Diethyl aminoethyl hexanoate reprogramed accumulations of organic metabolites associated with water balance and metabolic homeostasis in white clover under drought stress - Hassan, Muhammad Jawad; Najeeb, Atiqa; Zhou, Min; Raza, Muhammad Ali; Ali, Ummar; Cheng, Bizhen; Ling, Yao; Li, Zhou (Frontiers in Plant Science, 2024)
Diethyl aminoethyl hexanoate (DA-6) serving as a non-toxic and low-cost plant growth regulator is used for improving plant growth and stress tolerance, but the DA-6-mediated organic metabolites remodeling in relation to drought tolerance not well documented in crops. The aims of the present study were to evaluate impacts of DA-6 on physiological functions including osmotic adjustment, photochemical efficiency, oxidative damage, and cell membrane stability as well as organic metabolites remodeling in white clover (Trifolium repens) leaves based on the analysis of metabolomics. Plants were foliar treated with or without DA-6 and subsequently exposed to drought stress for 8 days. Results demonstrated that foliar application of DA-6 (1.5 mM) could significantly ameliorate drought tolerance, which was linked with better leaf water status, photosynthetic performance, and cell membrane stability as well as lower oxidative injury in leaves. Metabolic profiling of organic metabolites identified a total of 59 metabolites including 17 organic acids, 20 sugars, 12 alcohols, and 10 other metabolites. In response to drought stress, the DA-6 induced accumulations of many sugars and sugar alcohols (erythrulose, arabinose, xylose, inosose, galactose, talopyranose, fucose, erythritol, and ribitol), organic acids (propanoic acid, 2,3dihydroxybutanoic acid, palmitic acid, linolenic acid, and galacturonic acid), and other metabolites (2-oxazoline, silane, and glycine) in white clover. These altered metabolites induced by the DA-6 could perform critical functions in maintenances of osmo-protection, osmotic adjustment, redox homeostasis, cell wall structure and membrane stability when white clover suffered from water deficit. In addition, the campesterol and stigmasterol significantly accumulated in all plants in spite of the DA-6 pretreatment under drought stress, which could be an important adaptive response to water deficit due to beneficial roles of those two metabolites in regulating cell membrane stability and antioxidant defense. Present findings provide new evidence of DA-6-regulated metabolic homeostasis contributing to drought tolerance in leguminous plants.